Cover Image. (29th June 2020) - Provenzano, Aldesia; Palazzo, Viviana; Reho, Paolo; Pagliazzi, Angelica; Marozza, Annabella; Farina, Antonio; Zuffardi, Orsetta; Giglio, Sabrina
Abstract : The front cover image is based on the Research Letter Noninvasive prenatal diagnosis in a family at risk for Fraser syndrome by Aldesia Provenzano et al., https://doi.org/10.1002/pd.5700 . Abstract : The front cover image is based on the Research Letter Noninvasive prenatal diagnosis in a family at risk for Fraser syndrome by Aldesia Provenzano et al., https://doi.org/10.1002/pd.5700 .